Mammogram as a screening tool in breast cancer - Abugattas Saba, Julio (2015)
Breast cancer is the second most frequent malignant neoplasm in the world and the fifth cause of death from cancer in women. In Peru, breast cancer is second in incidence and the third cause of death from cancer in women. Mammography screening began in 1960 with the goal of detecting cancer at its smallest size before clinically evident in order to have better prognosis and survival. Several trials have been done since to determine mammography importance as a screening method and to establish age to begin, frequency and when to stop screening. In this article the role of mammography as screening tool is reviewed, as well as controversies on use, side effects, and recommendations on its use in Peru.